Infusion Therapy Optimization in Selective Abdominal Surgery - I. A. Smeshnoi; I. N. Pasechnik; E. I. Skobelev; D. A. Timashkov; М. A. Onegin; Yu. V. Nikiforov; S. I. Kontarev (Общая реаниматология)
Purpose. Evaluation of the influence of intra-operative targeted infusion therapy managed by the monitoring of stroke volume variability on post-operative results of major surgeries of gastrointestinal organs.Materials and Methods. The prospective study included 80 patients subjected to selective operative interventions of abdominal organs involving entero-enteroanastomosis. In the experimental group (n=39), the infusion therapy was conducted according to the developed targeted therapy protocol, of which the key parameter was stroke volume variability. In the control group (n=41), infusion therapy was conducted based on routine hemodynamic monitoring (average arterial pressure, heart rate, blood loss level with regard to intra-operative situation). In both groups, operative intervention was carried out in identical conditions (combined anesthesia, identical drugs to induce and maintain anesthesia); the only differences included infusion therapy.Results. In the experimental group versus the control group the intra-operative infusion volume was smaller, the number of patients with complications and the total number of complications were reliably lower, and the gastrointestinal tract functional recovery occurred earlier. Conclusion. A targeted infusion therapy based on a stroke volume variability monitoring as the key parameter allows optimizing the infusion load and facilitates reduction of the number of patients with complications and earlier recovery of gastrointestinal tract functions after major operative abdominal interventions.